Pengaruh Model Pembelajaran Talking Stick Terhadap Hasil Belajar Ilmu Pengetahuan Alam (Ipa) Siswa Kelas V Di UPTD SD Negeri 125549 Pematang Siantar - Netti Yuniarta Simatupang; Aprido B Simamora; Selamat Triadil Saragih (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the effect of the Talking Stick learning model on the learning outcomes of Natural Sciences (Science) for Class V students at UPTD SD Negeri 125549 Pematang Siantar. The design of this research is Pre-Experimental with the form of One-Group Pretest-Posttest Design. The population of this study was all class V UPTD students at SD Negeri 125549 Pematang Siantar, totaling 24 students. There are two hypotheses in this research, (1) there is an influence of the Talking Stick learning model on the learning outcomes of class V students in Theme 3